A Review, Translation, and Analysis on Kitāb al- Nagham: Yahaya ibn alMunajjim’s Account on Isḥāq alMawșilī - Ehsan Zabihifar; Seyed Shahin Mohseni (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی, 2022)
The current article presents a review, translation, and analysis on the brief and invaluable Kitāb al-Nagham of Yhaya ibn alMunajjim - a scientist in third century - in which there is Isḥāq alMawșilī’s account on the "Old School of Qina". This School, which existed before translating Greek books and is largely inspired by the pre-Islamic music, is much different, regarding the culture, from what alFarabi introduced. The core of this treatise is first to study the number the main notes and position them on the Oud and then explicating the notion of "Majrā" which was innovated by Isḥāq alMawșilī‘s analysis of the notation system indicates that the system is founded on ten notes which can develop into two Majrās: Binsir and Vustā consisting of eight and seven notes respectively. These two are different in at least two notes and have the other notes in common. The analysis also disproves what has been asserted so far and that Majrā is similar to mode and scale. The term “Imād” is introduced as the standard note to tune instruments accordingly. Terms such as “Saut” and “Tabaqa” which are used in the text have different meanings than what they denote today. The treatise also discusses the number and the purpose of oud’s strings. This treatise is one of the oldest works in theoretical music which has adopted an analytical approach and at the same time is similar to the practical tradition of music. This current article includes a translation of the original text in Persian, based on which a text-oriented analysis and an explication of alMunajjim’s ideas along with criticism of older accounts are presented.